INADEQUATE HUMAN RESOURCES AND THEIR EFFECT ON THE SERVICE DELIVERY OF ADAMAWA STATE PRIMARY HEALTH CARE DEVELOPMENT AGENCY - Ibrahim , Hassan Adebayo (Ayden International Journal of Law, Political Science, and Administration, 2024)
The effect of inadequate human resources on performance of Adamawa state primary health care Development agency, is very crucial for Effective delivery of Health care services the research is to investigated the effect of human resources inadequacy on work load of staff of the agency, personnel inadequacy impact the job satisfaction of employees at Adamawa State Primary Health Care Development Agency between 2015 and 2020, relationship between human resource inadequacy, the training and development of staff at Adamawa State Primary Health Care Development Agency. The research employed both qualitative and quantitative method of data analysis using regression and correlation analysis. the analysis revealed that a significant proportion of respondents perceived negative effects across various dimensions like timely access to care, patient outcomes, patient satisfaction, availability of essential equipment, and communication. This suggests inadequacy of staff training and development in Adamawa State Primary Health Care Development Agency, as well evaluate the financial implications of human resource inadequacy on Agency Operations. The study concluded that lack of staff training and development, as well as paucity of financial significantly compromised the performance of the Primary Health Care Development Agency from 20152020 across multiple domains. Personnel shortages had widespread detrimental effects on healthcare service access, quality, delivery, utilization, patient satisfaction, health outcomes and system productivity, and suggest that personnel shortages compromised quality, and therefore recommended that improve funding and investment into health workers training, compensation and benefit to attract and retain personnel.